PORTFOLIOS VS TESTS: RETHINKING ASSESSMENT IN SECONDARY ENGLISH EDUCATION - Kalandarova Mavluda Farxod qizi (International Journal of Literature and Language Studies, 2026)
The article explores the comparative effectiveness of traditional testing and portfolio-based assessment in secondary English language classrooms. While conventional tests ensure standardization and comparability, they often fail to reflect the multidimensional nature of language competence. Portfolio assessment, in contrast, emphasizes continuous development, learner reflection, and authentic communication. The paper argues that combining both approaches provides a more balanced and pedagogically sound assessment framework.